The Impact of (Lot Upon Dispute) Maxim on Judiciary - A Comparative Study between Islamic Jurisprudence and Positive Law in the Sultanate of Oman- - Al- fahdi, Fahad Khamis Ahmad (Journal of Economic, Administrative and Legal Sciences, 2020)
The importance of this research lies in identifying the significance of giving due regard to the jurisprudential maxims, especially those related to judicial work. Islamic jurists have paid attention to the maxim of “lot upon dispute” to console the souls and reconcile litigants. This maxim represents the highest and loftiest degrees of social interactions in the Islamic community depending on a prudent Quranic provision and wise prophetic Sunnah. This study is divided into three subjects: First: the definitions of study terms. Second: the researcher addresses the impact of the maxim in the judiciary literature and related topics in the code of procedures, personal affairs and civil transactions. Third: the researcher mentions some exceptions of maxim and the characteristic of lot, then clarifies the legal status of the maxim. The researcher concludes the study with the most important results, such as the jurisprudential maxim combines different issues in a phase of an eloquent meaning and precise wording. Jurists adopt this maxim more than the people of law do in order to achieve justice and block the accusation door. The study refers also to the necessity that those who work in the judiciary work should consider these jurisprudential maxims through establishment and application. Judge or arbitrator shall also act upon this maxim, and seek to reconcile between people through balloting. In addition, the specialized colleges and universities shall adopt the “lot upon dispute” maxim, and exert due diligence in studying it and any subdivided contemporary issues.
Keywords: jurisprudential rule; judiciary; law; lottery